Akibat Hukum Terhadap Wanprestasi Dalam Perjanjian Pemeliharaan Burung Walet Di Labuhan Lombok : Studi Kasus Putusan Pengadilan Negeri Selong Nomor 134/Pdt.G/2020 PN Selong - Septina Indi Huwaida; Salim HS (Private Law, 2022)
This study aims to determine the process of resolving cases on breach of contract of Swallow Bird preservation agreements based on the decision of the Selong District Court Number 134/PDT.G/2020 and the legal consequences arose from breaching the contract of of Swallow Bird agreement in Selong District Court Decision Number 134/PDT.G/2020. The type of research used on this study is normative law research, with the combination of statutory approach, conceptual approach, and analytical approach application method. The process of resolving cases in cases of breach of contract for Swallow Bird preservation is through the courts. The legal consequences that arise in the breach of contract of the Swallow Bird preservation agreement are the compensation given by the defendant to the plaintiff and the judge grants some of the claims filed by the plaintiff as the party experiencing default.